Flaxseed oil and clove leaf essential oil in Zebrafish diet (Danio rerio) - Silva, Thiberio Carvalho da; Silva, Michele; Carbonera, Fabiana; Visentainer, Jesui Vergilio; Utsunomiya, Karina Sayuri; Gasparino, Eliane; Ribeiro, Ricardo (Acta Scientiarum. Animal Sciences, 2020)
Flaxseed oil is recognized as the plant source richest in α-linolenic acid, whereas clove leaf essential oil has a strong antioxidant capacity. The objective of this study was to determine the in vitro antioxidant capacity of diets containing a combination of flaxseed oil (FO) and clove leaf essential oil (CLEO), as well as to use zebrafish (Danio rerio) to assess their effect on the animals’ growth. Fifty days after hatching, a total of 420 male specimens (0.29 ± 0.04 g) were divided into seven groups for each diet and fed for 55 days to be used, with the diets being: control, absent FO and CLEO; 3% FO + 0.5% CLEO; 3% FO + 1% CLEO; 6% FO + 0.5% CLEO; 6% FO + 1% CLEO; 9% FO + 0.5% CLEO and 9% FO + 1% CLEO. Antioxidant activity was determined through DPPH (2,2-diphenyl-1-picrylhydrazyl) tests, showing interaction effect between factors (FO x CLEO, p < 0.05); the diets containing 1% combined with 3, 6 or 9% of FO presented means higher than those of the 0.5% diets. No mortality was observed during the experiment. For final weight and weight gain, there was no interaction effect (p > 0.05), only isolated effect for FO, with the fish fed 6 and 9% diets having the best results. Final total length and specific growth rates showed interaction effect (p < 0.05). As for specific growth rates, the best response was that of the diet with 6% FO and 0.5% CLEO. Final length showed increase with FO levels, even when there was association with 0.5 or 1% of CLEO. Therefore, combined use of 9% of FL with 0.5% of CLEO is recommended for zebrafish.